Increased frequency of regulatory T cells in peripheral blood and tumour infiltrating lymphocytes in colorectal cancer patients - Khoon, L; Pratap, SE; Bates, G; Singh, B; Mortensen, N; George, B; Warren, B; Piris, J; Roncador, G; Fox, S; Banham, A; Cerundolo, V (2007)
Recent results have shown a correlation between survival and frequency of tumour infiltrating T lymphocytes in colorectal cancer patients. However, it remains unclear whether the frequency of regulatory T cells is higher in colorectal cancer as compared to normal colon. To address this question we analysed the frequency and function of regulatory T cells in the peripheral blood and tumour infiltrating lymphocytes of colorectal cancer patients. The proportion of regulatory T cells in the peripheral blood of colorectal cancer patients (mean 8%) was significantly higher than that in normal controls (mean 2.2%). There were significantly more regulatory T cells in tumour infiltrating lymphocytes (mean 19.2%) compared to lymphocytes from an autologous non-malignant portion of the colon (mean 9%). Regulatory T cells from colorectal cancer patients were FOXP3 positive and suppressed the proliferation of autologous CD4+ CD25- cells. A higher density of tumour infiltrating regulatory T cells was found in patients with advanced as compared to early disease. These results support the hypothesis that increased numbers of regulatory T cells in the blood and tumours of colorectal cancer patients may influence the immune response against cancer and suggest that strategies to overcome regulatory T cell activity may be beneficial in the treatment of human colorectal cancer. Copyright © 2007 by Vincenzo Cerundolo.